Optimalisasi Alokasi Sumberdaya Rumahtangga Petani Di Ekosistem Lahan Pasang Surut di Kalimantan Selatan = Optimizing The Allocation Of Farm-household Resources In Tidal Swamp Area In South Kalimantan - Emy Rahmawaty; Dibyo Prabowo; Slamet Hartono; Ismet Ahmad (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2003)
The objective of this research is to analyses the allocation of farmer household resources in tidal swamp area. The survey method was used to collect farmer data located in tidal swamps land villages with acid sulphate land, peatyland,. and potential land typologies in South Kalimantan. Quantitative analysis of data was carried out using linear programming model and sensitivity analysis, utilizing the BLPX 88 program.The findings of the analysis showed that villages allocated resources differently with the implication that incomes earned by the villages differed from one village to the other. However, it was found out too that optimal solution showed the need for the continuation of rice growing in the areas. Farmers who were located in potential areas where tangerine were grown produce higher incomes than the other two villages. To replicate the cropping pattern farmers in potential land in acid sulphate land and peatyland, resulted into a drastic increase in income earned by farmers